Adalimumab Biosimilar–Induced Autoimmunity-Related Sweet-Like Neutrophilic Dermatosis. (10th March 2023) - Lobato-Berezo, Alejandro; Pujol, Ramon M.; Fernández-Figueras, María Teresa
Abstract: Antitumor necrosis factor therapies have shown to produce a broad range of cutaneous eruptions. We report the case of a patient under adalimumab biosimilar treatment for a punctate inner choroidopathy who developed a cutaneous eruption on sun-exposed areas that showed a diffuse dermal neutrophilic infiltrate consistent with a Sweet-like neutrophilic dermatosis and some features of autoimmunity.